UNDERSTANDING INTELLECTUAL PROPERTY RIGHTS IN THE INDONESIAN TRADING BUSINESS - Maghfirah, Nurul; Zaviera, Siti; Alghazy, Daffa; Fahmi, Chairul (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2022)
This article aims to find out the concept of Intellectual Property Rights (IPR) in Indonesia and its application in business ventures. In general, Indonesia has recognised IPR and has passed a number of laws related to IPR protection. This research uses a literature approach method, where data is obtained from secondary sources, both from books, articles and various references related to this research. The results show that the application of IPR in Indonesia is still experiencing various problems, where many IPR results are violated. Conversely, law enforcement against IPR violations is still very weak. This is inseparable from the scope of IPR which is categorised as part of civil law. This means that if no one reports and feels harmed by the IPR violation, then the violation is not followed up or handled by the authorities.